2022
DOI: 10.3390/antiox11071285
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antioxidant Activities of Plants in Preventing Cataractogenesis

Abstract: A cataract is a condition that causes 17 million people to experience blindness and is the most significant cause of vision loss, around 47.9%. The formation of cataracts is linked to both the production of reactive oxygen species (ROS) and the reduction of endogenous antioxidants. ROS are highly reactive molecules produced by oxygen. Examples of ROS include peroxides, super-oxides, and hydroxyl radicals. ROS are produced in cellular responses to xenobiotics and bacterial invasion and during mitochondrial oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 125 publications
0
8
0
Order By: Relevance
“…Indonesia produces 40 types of essential oils; they are among the best known ones, including patchouli oil (PO), nutmeg oil, citronellal, ginger oil, and vetiver. 1,2 PO is an essential oil isolated from various plant parts in the Lamiaceae family; Pogostemon cablin Benth is a specific plant that only grows in parts of Southeast Asia such as Indonesia and the Philippines. The traditionally produced oil has been used for hundreds of years as aromatherapy and, since the 20th century, has been used as a fixative in the fragrance industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia produces 40 types of essential oils; they are among the best known ones, including patchouli oil (PO), nutmeg oil, citronellal, ginger oil, and vetiver. 1,2 PO is an essential oil isolated from various plant parts in the Lamiaceae family; Pogostemon cablin Benth is a specific plant that only grows in parts of Southeast Asia such as Indonesia and the Philippines. The traditionally produced oil has been used for hundreds of years as aromatherapy and, since the 20th century, has been used as a fixative in the fragrance industry.…”
Section: Introductionmentioning
confidence: 99%
“…The largest consumption of essential oils (35%) is in the food and beverages industry, followed by the fragrance and aromatherapy industry (29%), the household cleaning industry (17%), the pharmaceutical industry (16%), and others (3%). Indonesia produces 40 types of essential oils; they are among the best known ones, including patchouli oil (PO), nutmeg oil, citronellal, ginger oil, and vetiver. , …”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recently turned their attention to natural products as a result of the rising demand for natural green formulations and cosmetic items. With the notion of better safety and fewer adverse effects compared to their synthetic equivalents, their use is increasing constantly across the world [ 1 ]. In 2012, the global market for herbal cosmetics was $1500 billion and estimated to grow at a rate of 25% per annum in both developed and developing countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, the global market for herbal cosmetics was $1500 billion and estimated to grow at a rate of 25% per annum in both developed and developing countries [ 2 ]. The natural active ingredients used in these products have strong antioxidants, vitamins and other bioactive compounds that slow the skin aging process [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants produce a variety of phytochemical substances, or secondary metabolites, that are beneficial to health [ 8 ]. It was also reported that many medicinal plants have high antioxidant activity [ 9 ]. Phytochemical compounds found naturally in plants are powerful effectors of biological processes that can reduce disease risk via complimentary pathways.…”
Section: Introductionmentioning
confidence: 99%